Ù†Ø¸Ø§Ù… ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ù† Ø¨Ø¹Ø¯ Ø¹Ø¨Ø± Ø§Ù„Ø¥Ù†ØªØ±Ù†Øª ÙÙŠ Ø¬Ø§Ø¦ØØ© Ø§Ù„ÙˆØ¨Ø§Ø¡ ÙƒÙˆÙÙŠØ¯-Ù¡Ù© Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ù¡ Ø¨Ø³ÙˆØ±Ø§ÙƒØ±ØªØ§ - Yuliana Prativi; Muhammad Zaenuri (IAIN Batusangkar, Indonesia, 2021)
Online learning is a learning via internet without meeting face-to-face between teachers and students. This online learning system is relatively new, therefore teachers and students should adapt quickly. This study aims to determine the online Arabic learning system during the COVID-19 pandemic at Madrasah Tsanawiyah Negeri (MTsN) 1 Surakarta. Researcher used a qualitative approach and observation, interview, and documentation as data collection techniques. The results described that e-learning madrasah was used as the main media for online Arabic learning at MTsN 1 Surakarta during the covid-19 pandemic, then assisted by Whatsapp and Youtube channel. The subject matter was presented in video, powerpoint, and pdf. The learning stages were divided into three: preparation, implementation (pre-activities, whilst-activities and post-activities), and evaluation stage. This online learning helps teachers to coordinate with and supervise students easily, on the other hand, it is difficult for them to monitor the studentsâ€™ understanding and bad internet network make some students could not follow the learning process in time.Â